Approaches to participation and knowledge equity in agricultural climate impacts modelling: A systematic literature review - Sarku, Rebecca; Challinor, Andrew J.; Jennings, Stewart; Whitfield, Stephen (University of Leeds, 2024)
The importance of participation and co-development in the study of climate change impacts and adaptations, and in the production of climate services is widely acknowledged. There is a lot to be learnt from current attempts to achieve participatory modelling in climate impacts science. In this systematic review of 84 papers that focus on climate impacts in agriculture, we map out, within existing efforts, how participation is achieved, with whom and at what stages of the modelling process. We also look at the extent to which challenges and issues around inclusion and marginalisation are encountered and critically reflected on within this literature. The review contributes to addressing the overarching question: what are the approaches for and barriers to improving participation in climate impacts modelling? This systematic review is guided by a framework that brings together critical work on power and typologies of participation (White, 1996) and a participatory modelling process framework (outlined by Voinov et al., 2016). We reflect on conventional and best practices and reveal areas in which there is currently insufficient attention given in order to encourage a more critical reflection on the design and implementation of participatory modelling. The black box nature and mechanics of climate impacts models creates barriers to participation and knowledge equity that can only be overcome by rethinking what and whom climate impacts modelling is for, and the linear, stepwise nature of its knowledge production. We argue that there is a current pre-occupation within participatory climate impacts modelling literature on instrumental reasons for including stakeholders and on technical barriers to this inclusion. Limited attention is currently paid to the potential transformative and emancipatory nature of participation in climate impacts modelling and there is a need for more critical reflection on the knowledge politics and power dynamics that act to limit equitable participation in such research.